Period-doubling route to chaos in a two-degree-of-freedom flexibly-mounted rigid plate placed in water. (August 2015) - Pourazarm, Pariya; Lackner, Matthew; Modarres-Sadeghi, Yahya
Abstract: Flow-induced instabilities of a flexibly-mounted rigid flat plate placed in water were investigated experimentally, when the plate had either one degree of freedom in the torsional direction or two degrees of freedom in the torsional and transverse directions. Tests were conducted in a re-circulating water tunnel and bifurcation diagrams were used to summarize the system behavior. The 1DoF system became unstable by divergence at a critical flow velocity after which the plate buckled. At higher flow velocities, periodic oscillations were observed and the amplitude of oscillations increased with increasing flow velocity. No other instability was observed at higher flow velocities. In the 1DoF system, the variations in the response frequency were related to the added mass moment of inertia. For the 2DoF system, the plate׳s original stability was lost at a critical flow velocity by divergence followed by a dynamic instability resulting in periodic oscillations, which in turn became unstable giving rise to period-2, period-4 and eventually chaotic oscillations.